Do better paid politicians perform better? Disentangling incentives from selection - Stefano Gagliarducci; Tommaso Nannicini (Institute for the Study of Labor (IZA), 2009)
The wage paid to politicians affects both the choice of citizens to run for an elective office and the performance of those who are appointed. First, if skilled individuals shy away from politics because of higher opportunities in the private sector, an increase in politicians' pay may change their mind. Second, if the reelection prospects of incumbents depend on their in-office deeds, a higher wage may foster performance. We use data on all Italian municipal governments from 1993 to 2001 and test these hypotheses in a quasi-experimental framework. In Italy, the wage of the mayor depends on population size and sharply rises at different thresholds. We apply a regression discontinuity design to the only threshold that uniquely identifies a wage increase - 5,000 inhabitants - to control for unobservable town characteristics. Exploiting the existence of a two-term limit, we further disentangle the composition from the incentive component of the effect of the wage on performance. Our results show that a higher wage attracts more educated candidates, and that better paid politicians size down the government machinery by improving internal efficiency. Importantly, most of this performance effect is driven by the selection of competent politicians, rather than by the incentive to be reelected.
Keywords: M52; D72; J45; H70; 330; Political selection; efficiency wage; term limit; local finance; regression discontinuity design; Politiker; Effizienzlohn; Leistungsmotivation; Kommunalverwaltung; Gemeindefinanzen; Haushaltskonsolidierung; Italien